Pendekatan Komunikasi Guru Kepada Siswa Tunanetra Majemuk Dalam Proses Pembelajaran di Yayasan Pendidikan Dwituna Harapan Baru - Wardani, Dila (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2025)
The problem faced by teachers towards students with multiple visual impairments is the obstacles in communicating so that it often hinders the learning process. the research entitled Teacher Communication Approach to Students with Multiple Visual Impairments in the Learning Process at Yayasan Pendidikan Dwituna Harapan Baru aims to provide a concrete description of how the communication approach taken by teachers to students with multiple visual impairments in the learning process at Yayasan Pendidikan Dwituna Harapan Baru. Multiple blindness is a condition of individuals who experience visual impairment (blindness) along with other disabilities, such as hearing impairment, intellectual impairment, motor impairment, or a combination of several of these conditions. This research uses descriptive qualitative method with data collection techniques through in-depth interviews, observation, and documentation. The informants in this study are teachers who teach at Yayasan Pendidikan Dwituna Harapan Baru. The data analysis technique was carried out with the stages of data reduction, data presentation, and conclusion drawing based on the findings in the field. The results showed that the communication carried out by the teacher was tailored to the needs and conditions of each student. such as touch, communication aids, and routine activities that help students more easily understand the lesson. the process in the teacher's communication approach to compound blind children consists of 5 approaches, namely: openness, empathy, support, a positive learning atmosphere, and equality